If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4-y)3=-9
We move all terms to the left:
(4-y)3-(-9)=0
We add all the numbers together, and all the variables
(-1y+4)3-(-9)=0
We add all the numbers together, and all the variables
(-1y+4)3+9=0
We multiply parentheses
-3y+12+9=0
We add all the numbers together, and all the variables
-3y+21=0
We move all terms containing y to the left, all other terms to the right
-3y=-21
y=-21/-3
y=+7
| 3/5y-1/6=-2/5y-1/3 | | 1/2(2n+6=5n-12-n | | −19x+-38=−19x+-38 | | 1/4-9x=6 | | 5x+17=4x+12 | | 8r+3-1+7r=6 | | 192+x=458 | | 80m=40 | | -7/d=6 | | -2x+-3x=3x+4 | | n/3+10=12 | | 6(5v-2)=-12-3v | | -5h-17=-8(h+4) | | -7=-4(p+8)+3(-p-8 | | 1/2x+17=4x+2 | | y=12*9+5 | | −68x+68=-68x+34 | | -5h-17=-8(h=4) | | 2/x+5=x+8/9 | | 4(5x-10)+2(2x+10)=124 | | -7(6x+4)+3(4-x)=-61 | | X+1/12=5/6+x-2/3 | | 0.025p-1=0.15(p-5) | | 7(m-4)(m+1)=-34 | | 58-3a=10 | | 59=2-3(4x+1) | | -5t+7=11t-24 | | 4y-(-3)=-25 | | 3/x+12=53 | | 3n=6n-3(5n+4) | | 7x-5=5(x-2)+13 | | 0=7(3n-7)-4(-8n+1) |